Research on Financial Risk Assessment and Control based on New energy vehicle manufacturing industry - Jian, Yangyang; Liang, Keke; Lin, Yuxuan; Liu, Dan (LPPM STIKI Malang, 2024)
This paper analyzes the differentiated growth path and business strategy effect of new energy car manufacturing companies NIO, Xiaopeng and Lixiang. Starting with financial performance analysis, Z-Score model is used to analyze the yearly changes of X variable and Z value of the three companies based on their financial data from 2019-2023, and carry out financial capability analysis and financial risk assessment. In the market environment of intensified competition, this paper explores the common problems of new energy car making new power companies, improves the system of measures in order to help enterprises reduce financial risks, maintain stable operations, and provide a reference for many new energy automobile manufacturing companies.